The Effect of Disclosure of Financial Reporting Information on The Level of Public Trust in Government Institutions - Bintang, Krista D.O; Sabrina, Indri; Samosir, Joy Tracy (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
This study aims to analyze the effect of disclosing financial reporting information on the level of public trust in government institutions. The background of this research is the disclosure of financial reporting information and the variables that influence it. This research method uses primary data, namely data obtained from surveys conducted through questionnaires distributed to respondents. The questionnaire used is a type of choice with a scale that is given a score (value) for each category. The main findings show that there are variables X1, X4, and X5, H0 is accepted and H1 is rejected or in other words these five variables do not significantly affect the level of trust in government institutions. And there are also variables X2 and X3, H0 is rejected and H1 is accepted or in other words these two variables significantly affect the level of trust in government institutions